2015
DOI: 10.1021/ic502051y
|View full text |Cite
|
Sign up to set email alerts
|

Selective Lability of Ruthenium(II) Arene Amino Acid Complexes

Abstract: A series of organometallic complexes of the form [(PhH)Ru(amino acid)](+) have been synthesized using amino acids able to act as tridentate ligands. The straightforward syntheses gave enantiomerically pure complexes with two stereogenic centers due to the enantiopurity of the chelating ligands. Complexes were characterized in the solid-state and/or solution-state where the stability of the complex allowed. The propensity toward labilization of the coordinatively saturated complexes was investigated. The links … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…16 Upon addition of 1 equivalent of L-His, an adduct was observed, consistent with replacement of H 2 O for L-His, binding though an imidazole N. When the sample was subjected to a second equivalent of L-His and left to equilibrate over 16 h, a species formed in which the pyridylphosphinate ligand is displaced and the L-His binds κ 3 (Figure 7). The observed Ru-(L-His) complex, 1c, is known to be non-cytotoxic 31 and its formation presents a potential explanation of the low cytotoxicity of Ru chloride complexes described in this report. It follows that the higher cytotoxicity of the iodide-complexes, 10, 21 and 22, is due to the metal-iodide bond being less labile towards aquation and therefore less likely to undergo decomplexation by chelating biomolecules.…”
Section: Binding Studiessupporting
confidence: 52%
“…16 Upon addition of 1 equivalent of L-His, an adduct was observed, consistent with replacement of H 2 O for L-His, binding though an imidazole N. When the sample was subjected to a second equivalent of L-His and left to equilibrate over 16 h, a species formed in which the pyridylphosphinate ligand is displaced and the L-His binds κ 3 (Figure 7). The observed Ru-(L-His) complex, 1c, is known to be non-cytotoxic 31 and its formation presents a potential explanation of the low cytotoxicity of Ru chloride complexes described in this report. It follows that the higher cytotoxicity of the iodide-complexes, 10, 21 and 22, is due to the metal-iodide bond being less labile towards aquation and therefore less likely to undergo decomplexation by chelating biomolecules.…”
Section: Binding Studiessupporting
confidence: 52%
“…Very few studies in which protonation of the binding functional group in the tether plays an important role in the dynamics of the metal–tether bond in aqueous solution have been reported . Pizarro et al.…”
Section: Resultsmentioning
confidence: 93%
“…Very few studies in which protonation of the binding functional group in the tether plays an important role in the dynamics of the metal-tether bond in aqueous solutionh ave been reported. [7,21,23] Pizarroe tal. reported the synthesis of [Ru{h 6 -C 6 H 5 (C 6 H 4 )NH 3 }Cl 3 ]f rom its closed-tether counterpart [Ru{h 6 :k 1 -C 6 H 5 (C 6 H 4 )NH 2 }Cl 2 ], by suspending the former in concentrated HCl (ca.…”
Section: Activation Undera Cidicconditionsmentioning
confidence: 99%
“…The closed form of the complexes, achieved through an arene ligand η 6 :κ 1 -C6H5(C6H4)NH2 coordination mode ( Figure 1D), dominates The pH-dependent intramolecular chelation of a range of ligands in half-sandwich ruthenium complexes to regulate ligand coordination at the ruthenium center has also been explored. Scrase et al reported that a L-2,3-diaminopropionic acid ligand coordinated in a tridentate manner to a ruthenium-η 6 -arene moiety was found to be labilized on lowering of pH, leading to partial reactivity of the complex on incubation with a protected methionine ligand at pH 2.5 [12]. Pizarro et al have shown reversible intramolecular chelation can be achieved in half-sandwich ruthenium complexes utilizing an hemilabile 2-aminobiphenyl arene ligand [13].…”
Section: Introductionmentioning
confidence: 99%